A COMPARATIVE CHEMICAL STUDY OF Pistacia Vera L.CULTIVARS CULTIVATED IN NINAVAH GOVERNORATE - Amer M.Mahmoud (Mesopotamia Journal of Agriculture)
The present work includes a chemical comparative study of Pistacia vera L. (Anacardiceae) which resemble (13) cultivars ( Ashoury, White ashoury , Nab Al Dajamal , Ajamy , Oleimy , Boundouky , Red Jalab , Turkey , Baidy , Lazwardy , Sen Al-Feel , Marawhy , Batoury ) are growing in Ninavah Gross Morphological , chemistry and location of cultivers distribution were conducted per each cultivars of the obove species and with taxonomic key for Identification . The results of this chemical study showed clear and distinct variations among studied cultivars in the nut contents from moisture , protein , oil , and phenolic compounds, the moisture ranged between (25.15 – 36.5%) the average of moisture in pistachio studied cultivars was about (31.96%) , the percentage of oil were varied and a clear variation among cultivars so we may be divided into three groups , the percentage of oil ranged between (49.65 – 68.90%), the average of oil in all studied cultivars was (58.83%) , the cultivars Ashoury was characterized by high oil percentage (68.90%) , the percentages of protein in cultivars don't showed high variation , the higher percentage of protein ranged a bout (25.15%) in cultivars ( Sen Al Feel) , while the lower percentage was found in cultivars Oleimy ( 18.25%). The average of protein in all studied cultivars were ranged (21.51%) . Results of the chemical study showed that (9) phenolic compounds (Quercetin- 7 – glucoside ، Myricetine ، Rutin ، Syringic Luteolin , Kaempferol Ferulic acid ، Catechol and Apigenin ) which were variable among various cultivars of the species studied . Also these results showed that the phonolic compound luteolin was found in the most of the studied cultivars which means that the studied cultivars are belong to one taxa and it reinforces the cultivars of one species .